Managerial overconfidence and corporate financing decision: The moderating effect of government ownership - Irene, Wei Kiong Ting; Hooi, Hooi Lean; Qian, Long Kweh; Noor Azlinna, Azizan (2014)
This paper investigates the impact of managerial overconfidence on corporate financing decision for publicly listed companies in Malaysia for the period of 2002-2011. Pooled OLS, fixed effect method (FEM) panel models and Tobit regressions are employed to examining the relationship between managerial overconfidence, government ownership, and leverage decision of publicly listed companies in Malaysia. This is the first study that empirically examines the impact of managerial overconfidence by testing CEO personal characteristics as a main independent variable on corporate financing decision for Malaysian firms. We also make the first attempt to test the moderating effect of government ownership on the relationship of managerial overconfidence and leverage decision. We conclude that (1) CEO overconfidence is significantly and negatively related to corporate financing decision and it is consistent with prior studies. (2) A higher degree of managerial overconfidence would result in lower leverage in GLCs, whereas the effect does not significantly exist in NGLCs. (3) A larger ownership of government in a firm will reduce the negative effect of managerial overconfidence on corporate financing decision. The finding implies that moderating effect of government ownership on the association between managerial overconfidence and corporate financing decision in GLCs is more effective than NGLCs.